A preface to Chaucer : studies in medieval perspectives. - Robertson, D. W., Jr. (Durant Waite), 1914-1992 (Princeton legacy library., 1962)
What were the medieval stylistic, aesthetic, and literary conventions that Chancer drew upon and knew that his audience would understand? In this rich study Mr. Robertson has included 118 illustrations-of medieval sculpture, cathedral interiors, illuminated manuscripts, paintings, ornamental devices and decorations-to show how these conventions affected the visual arts of Chaucer's time. Special attention is directed to fundamental differences between medieval and modern attitudes toward poetry, and to the significance of these differences for an approach to medieval art. By placing Chaucer fully in his own time, Mr. Robertson establishes new perspectives for understanding Chaucer's poetry. His book is like a rich tapestry weaving together many threads. Originally published in 1962. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.